Utility of neck dissection for management of carcinoma of the parotid gland. Issue 10 (December 2019) - Kaura, A.; Kennedy, R.A.; Ali, S.; Odell, E.; Simo, R.; Jeannon, J.P.; Oakley, R.
Abstract: To validate the use of neck dissection as part of the management of patients with parotid carcinomas, we retrospectively reviewed pathological and clinical data from the head and neck pathology archive at Guy's and St Thomas' Hospital on all patients who had primary parotid carcinomas resected between 1992 and 2014. The main outcome measure was the incidence of metastatic disease. A total of 54 of the 82 patients identified had neck dissections. Nodal metastases were detected in 10 with high-grade, invasive carcinoma ex-pleomorphic adenomas, two with salivary duct carcinomas, one with a high-grade adenocarcinoma not otherwise specified (NOS), one with an adenoid cystic carcinoma, and one with a high-grade acinic cell carcinoma. No metastases were found in those with a low-grade acinic cell carcinoma, low-grade mucoepidermoid carcinoma, epithelial-myoepithelial carcinoma, or non-invasive carcinoma ex-pleomorphic adenoma. The findings of this study support the use of routine neck dissection for the treatment of high-grade, invasive carcinoma ex-pleomorphic adenoma, salivary duct carcinoma, high-grade adenocarcinoma NOS, adenoid cystic carcinoma, and high-grade acinic cell carcinoma.